The Impact of Tharthar - Euphrates Canal Salinity on the Quality of Euphrates River near Fallujah, Iraq - Al-Sammarrai , Zainab; Al-Dabbas, Moutaz (Iraqi Journal of Science, 2026)
The Tharthar Euphrates Canal adds considerable dissolved material to the Euphrates River near Fallujah. Hence, this study aims to examine the variations of solute concentration within the Tharthar-Euphrates canal and estimate the quantitative production of dissolved matter transported to the Euphrates River near Fallujah city. Ten water samples were taken in 2024 along the canal and the Euphrates River to examine the dissolved material in the Tharthar-Euphrates canal, evaluate the water's physicochemical characteristics, and determine the dissolved load carried through the channel. Historical salinity (TDS) and the chemical constituent ions, Cl‾, SO42-, HCO3‾, Na+, Ca2+, Mg2+, and K+ of the Tharthar-Euphrates canal, were supplied by the Ministry of Water Resources for the hydrological years 2018 to 2023 for the dissolved load calculation that was carried out through the Tharthar-Euphrates canal. A slight increase in dissolved solid concentration was observed downstream of the canal. None of the water samples were helpful for drinking.  The water types have indicated that sulfate ions are the dominant ions in the canal.  Meanwhile, the Euphrates River water indicates that sulfate and bicarbonate ions are common in the water. The solute concentrations in the Tharthar-Euphrates canal water were plotted with the canal discharge to the Euphrates River from 2018 to 2024. The rating curve has been plotted, showing a strong positive correlation between the Tharthar-Euphrates Canal discharge and the dissolved loads.